(untitled) (International Journal of Physiotherapy, 2016)
Background: Clinical reasoning is a process by which physiotherapists interacted with patients, their family and other health- care professionals. It is the thinking process that professionals tend to apply in clinical practice. Given that novice as well as expert practitioners prefer to go through some steps while they were dealing with unfamiliar cases. This process is known as hypothetico deductive reasoning. This reasoning approach involved the generation of hypothesis based on clinical data and knowledge and testing of hypothesis through further inquiry. We are expert in musculoskeletal physiotherapy treatment and favoring the atypical history of patient we went through step by step from assessment to discharge Methods: A case based study through hypothetico deductive reasoning model of clinical reasoning. The objective of the study was to investigate the physiotherapy management strategies of an atypical ankle sprain patient through hypothetico deductive reasoning which comprised of cue acquisition, hypothesis generation, cue interpretation and hypothesis evaluation by implementing International Classification of Functioning, Disability and Health (ICF). Results: The patient responded well to treatment as patient reported that 100% swelling decreased, could bear more weight (95%) on foot, decrease pain (1 cm on 10 cm VAS scale), improved muscle strength by manual muscle testing by grade V in ankle planter flexors (PF) as well as dorsiflexors (DF), invertors as well as evertors and the functional status of patient was improved by 80% according to lower extremity functional scale. Conclusion: Clinical reasoning is an important approach in physiotherapy. It helps the practitioners in decision making and choosing the best alternative options for the well being of patients. We think it is necessary for all practitioners to have sound propositional and non-propositional knowledge in order to provide effective management protocol for patients focusing ICF. Even though we have been treating patients with musculoskeletal problems on regular basis, the atypical pattern of this patient give us the impression not to use pattern recognition all time for all patients rather using hypothetico deductive reasoning (HDR) where appropriate.